Effects of Overexpression of the Egyptian Fruit Bat Innate Immune Genes on Filovirus Infections in the Host Cells - Kuzmin, Ivan V.; Ramanathan, Palaniappan; Basler, Christopher F.; Bukreyev, Alexander (Frontiers in Virology, 2021)
Bats constitute a large and diverse group of mammals with unique characteristics. One of these is the ability of bats to maintain various pathogens, particularly viruses, without evidence of disease. The innate immune system has been implicated as one of the important components involved in this process. However, in contrast to the human innate immune system, little data is available for bats. In the present study we generated 23 fusion constructs of innate immune genes of Egyptian fruit bat (Rousettus aegyptiacus) with mCherry as a fluorescent reporter. We evaluated the effects of overexpressing these genes on the replication of Marburg and Ebola viruses in the Egyptian fruit bat cell line R06EJ. Both viruses were substantially inhibited by overexpression of type I, II and III interferons, as well as by DDX58 (RIG-I), IFIH1, and IRF1. Our observations suggest that the broad antiviral activity of these genes reported previously in human cells is conserved in Egyptian fruit bats and these possess anti-filovirus activities that may contribute to the efficient virus clearance.